The mysterious human heart. 3, The silent killer [videorecording (DVD)] - Grubin, David (Ambrose Video, 2007)
Each of the three programs that make up "The mysterious human heart focuses on a different aspect of what we thought we knew, what we know now, and what we're on the verge of learning about the heart. This material is presented through the real-life dramas of people who suddenly learn that a normal, functioning heart is not something that can be taken for granted. In episode 3, the focus is on atherosclerosis, the silent blockage of the coronary artieries, which can trigger devastaiting and sometimes fatal heart attacks.